2018
DOI: 10.1186/s13014-018-1183-y
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of concurrent chemoradiotherapy versus chemotherapy alone for stage IV esophageal squamous cell carcinoma: a retrospective controlled study

Abstract: BackgroundThe purpose of this study is to compare the efficacy and safety of concurrent chemoradiotherapy (CCRT) versus chemotherapy alone for patients with stage IV esophageal squamous cell carcinoma (ESCC).MethodsEligible patients were retrospectively enrolled at the authors’s institution from January 2010 to October 2015. Of the 141 patients enrolled, 55 (39.0%) received CCRT and 86 (61.0%) received chemotherapy alone. The outcomes and adverse events (AEs) were compared between the two groups.ResultsThe bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Cisplatin (CDDP) is a platinum agent commonly applied for ESCC, and its application, with and without other agents, has led to a noticeable improvement in prognosis 5 . Nevertheless, acquired resistance to chemotherapy is a frequent cause of treatment failure 6,7 . Consequently, avoiding resistance is crucial for prognosis 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin (CDDP) is a platinum agent commonly applied for ESCC, and its application, with and without other agents, has led to a noticeable improvement in prognosis 5 . Nevertheless, acquired resistance to chemotherapy is a frequent cause of treatment failure 6,7 . Consequently, avoiding resistance is crucial for prognosis 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Another retrospective study of 198 stage IV ESCC patients reported that the CRT group had a longer median OS (14.0 months vs. 11.0 months, p = 0.007) than the chemotherapy group (74.5% versus 45.3%, p = 0.001). Multivariate analysis identified CRT (CRT vs. chemotherapy: HR = 0.626, 95% CI: 0.437–0.898, p = 0.013) and solitary metastasis (solitary vs. multiple metastasis: HR = 0.621, 95% CI: 0.426–0.905, p = 0.037) as independent factors for better OS in this study ( 24 ). The number of metastases may also be a prognostic factor, but it was not provided from the SEER database in our study.…”
Section: Discussionmentioning
confidence: 55%
“…A Korean multi-institutional cohort study showed similar data that with multiple treatment modalities, the 5-year OS rate was about 16.6%, and mOS was 0.9 years ( Jung et al, 2020 ). In China, a retrospective controlled study reported that the 3-year OS rate of advanced-stage EC patients was about 4.7%–10.7%, and the mOS was about 11–14 months ( Lyu et al, 2018 ). In our study, even though the 5-year OS seemed similar among all eligible subjects, the higher OS rate among CHM users revealed the possibility of integrating CHM with palliative management.…”
Section: Discussionmentioning
confidence: 99%